Analysis of Factors Affecting the Level of Cash Holdings on Non-Financial Companies - Rahmadhani, Sari; Taswan, Taswan; Bhandari, Rahul; Rusli, Muhamad Saufi Che; Astillero, Marlon Rael; Irawan, Nico; Miftakhurniyati, Miftakhurniyati (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The existence of cash in a company's financial balance sheet is an important component. Without cash, the company's activities will not be able to run. This research aims to analyze and provide empirical evidence regarding the influence of growth opportunity, net working capital, cash conversion cycle, cash flow, and firm size on cash holding in non-financial companies listed on the Indonesia Stock Exchange, Stock Exchange of Thailand and National Stock Exchange of India in 2018-2022. This research uses secondary data collected. The data used is non-financial company financial report data from 2018-2022. The sample for this research was taken using a purposive sampling technique, namely determining samples that met certain criteria so that 269 companies were used as samples in this research. The research data was then analyzed using Partial Least Square (PLS-SEM). Based on the test results using statistical tests, it shows that the growth opportunity and firm size variables have a significant negative effect on cash holding, the net working capital and cash flow variables have a significant positive effect, while the cash conversion cycle variable does not affect cash holding.